VERIFIKASI METODE ANALISIS METAMFETAMINA DAN AMFETAMINA DALAM MATRIKS URIN SECARA AUTOMATISASI DENGAN GERSTEL® DISPOSABLE PIPETTE EXTRACTION (DPX) MULTIPURPOSE SAMPLER (MPS) - Prisma Andini Mukti; Sulaeman Mappasessu; Yuswardi Mappasessu; triwidiastuti Andini Mukti; Dwi Hernanto; Brahmanti Adjiesaka; Muhammad Genta Zuan Nur (Journal of Forensic Expert, 2021)
Method analytical validation and verification is crucial in routine qualitative and quantitative analysis. Analysis laboratory need objective evidences about specific parameters in their drugs/analytes or drugs metabolites in matrices biology. Urine is the most preferable matrix biology for determining drugs metabolites especially in drug abuses cases because urine’s sampling process is not invasive. There are many methods extracting drugs in urine, especially methamphetamine and amphetamine as those two analytes are excreted via urine. This study presented method verification for determination of methamphetamine and amphetamine in urine using Gerstel® automated Disposable Pipette Extraction (DPX) Multipurpose Sampler (MPS). Result of this study showed that retention time of methamphetamine is in minute 6.21, and amphetamine is in minute 3.15. Methampethamine’s curve displayed a coefficient of determination r2=0,9999 with the equation y=170,19x+33183. The equation of amphetamine showed y=44390x – 17513 with coefficient of determination r2= 0,9974. Limit of detection (LOD) of methamphetamine in urine is 59,73 ppb, and LOD of amphetamine is 36 ppb.